Faktor-Faktor Pendukung & Penghambat Implementasi Program Corporate Social Responsibility dalam Membantu Kehidupan Masyarakat Sekitar Perkebunan - Rizka Rahmah Hidayati; Badaruddin Badaruddin; R. Hamdani Harahap (Universitas Medan Area, 2021)
This research aims to analyze the supporting & barrier factors of the implementation of corporate social responsibility program of PT. PP London Sumatra Indonesia, Tbk in helping the lives of the people around Bagerpang Plantation, Deli Serdang Regency - North Sumatra Province. Research methods are carried out with a qualitative approach using data collection techniques through interviews and field observations. The informants in this study consisted of CSR program recipients, corporate management who handle CSR departments and local village government apparatus. The research site covers Bagerpang estate which consists of 7 divisions / villages in 3 sub-districts namely Galang, Bangun Purba and STM Hilir. The results showed that PT. PP London Sumatra Indonesia, Tbk as a private company in the field of agro industry participated in assisting the government in development through the implementation of CSR programs as a form of social responsibility to the community and the environment for the impact sparked by its operational activities. PT. PT. PP London Sumatra Indonesia, Tbk has implemented CSR practices in several areas of work, namely education, health, infrastructure maintenance, social and religious and populist economic efforts. Researcher also introduced several supporting and barrier factors of the success and effectiveness of CSR implementation. The conclusion of this research is that the company is still focusing its CSR implementation goals and objectives on improving the quality of life of employees and their families not yet on the level of community empowerment._________________________________________________________________________